Islanding detection method adopting single‐phase‐operating circuit breaker. Issue 4 (1st March 2016) - Shang, Yuwei; Shi, Shenxing
Abstract : This study proposes a novel islanding detection method adopting single‐phase‐operating circuit breaker (CB). The method aims to utilise the operation of CB to generate specific electric information to the distributed generator (DG), instead of using a dedicated signal generator at the substation. When islanding forms, the CB opens three‐phase circuits asymmetrically to indicate the islanding, which causes asymmetric operation of the local system within a predefined short time. During this period, negative‐sequence voltage with certain duration is obtained at DG side. Furthermore, the varying characteristics of three‐phase voltages from close status to open status of CB are the same, which can be utilised to distinguish the formation of islanding from system disturbances. The method is tested based on a typical medium‐voltage distribution network with synchronous DG interconnection. Test results show the effectiveness of the proposed method under both islanding formation and system disturbance scenarios.